2016
DOI: 10.1590/1677-5449.002316
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of atherosclerosis with panoramic radiographs: a review

Abstract: Carotid artery disease has been linked with cerebral vascular accident, also known as stroke, cerebral hemorrhage, or cerebral ischemia. It is caused by narrowing or obstruction of arteries in the neck (the carotid arteries) that are responsible for transporting blood from the aorta to the brain. Panoramic radiographs are used in dentistry to show both dental arches as a supplement to the clinical dental examination. The objective of this study is to highlight the importance of panoramic radiographs for diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
3
0
6
Order By: Relevance
“…EPL strengthened the endothelium-dependent relaxation and suppressed angiotensin-converting enzyme activity in the vasculature, which further prevented the development of atherosclerosis (24). Another study has previously found that IVUS can produce qualitative and quantitative images with high accuracies of plaque morphology identification in atherosclerosis lesions (5). In the present study, Gd 2 O 3 -EPL nanoparticles were introduced and it was found that the addition of Gd 2 O 3 -EPL enhanced the IVUS signals in evaluating the revascularization decision of intermediate and ambiguous coronary lesions.…”
Section: Discussionmentioning
confidence: 98%
“…EPL strengthened the endothelium-dependent relaxation and suppressed angiotensin-converting enzyme activity in the vasculature, which further prevented the development of atherosclerosis (24). Another study has previously found that IVUS can produce qualitative and quantitative images with high accuracies of plaque morphology identification in atherosclerosis lesions (5). In the present study, Gd 2 O 3 -EPL nanoparticles were introduced and it was found that the addition of Gd 2 O 3 -EPL enhanced the IVUS signals in evaluating the revascularization decision of intermediate and ambiguous coronary lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Vale la pena señalar que la radiografía panorámica no es prueba de diagnóstico para la detección temprana de la aterosclerosis carotídea, y calcificaciones en los tejidos blandos que aparecen son por lo general los hallazgos incidentales, por lo que es importante que el profesional sepa como evaluar e interpretar estas imágenes y no confundir con otras estructuras (Almog et al, 2005;Atalay et al;Borba et al;Abreu et al).…”
Section: Discussionunclassified
“…A pesar de esto, el valor de la radiografía panorámica cuando se visualizan calcificaciones carotídeas no debe disminuirse. La radiografía panorámica de la cara es una prueba de bajo costo y, aunque no debe usarse como método de diagnóstico inicial en la búsqueda de calcificaciones carotídeas, puede ser una herramienta importante para detectar calcificaciones en las arterias carótidas (Almog et al, 2004;Roldán-Chicano et al;Ramesh & Pabla;Atalay et al;Borba et al).…”
Section: Discussionunclassified
See 2 more Smart Citations